Mechanistic insights into the pseudocapacitive performance of bronze-type vanadium dioxide with mono/multi-valent cations intercalation. Issue 19 (25th April 2022) - Zeng, Ying; Hu, Jian; Yang, Jiaofeng; Tang, Pei; Fu, Qingfeng; Zhou, Wang; Peng, Yufan; Xiao, Peitao; Chen, Shi; Guo, Kunkun; Gao, Peng; Dong, Hongliang; et al.
Abstract : Mechanistic understanding of mono/multi-valent cations' behaviors upon intercalation into solvothermally prepared VO2 (B), which enables rational design of layered oxides with excellent charge storage performance. Abstract : Bronze-type vanadium dioxide (VO2 (B)) is a promising intercalation pseudocapacitive material due to its special corner and edge-sharing structure. Meanwhile, the utilization of multivalent cations as charge carriers has been considered an effective strategy to further improve its charge storage capability. However, the mechanistic understanding of multivalent cations' intercalation into VO2 (B) is still vague, which greatly limits its practical application. Via a combination of structure characterization, theoretical calculations and electrochemical analysis, we have shown that only ion (de-)intercalation into VO2 (B) occurs in Na2 SO4 and MgSO4 electrolytes upon cycling, and their distinct charge storage performance is considered due to the synergistic effects between the ionic radius of electrolyte cations and their polarizing power. In contrast, part of VO2 (B) is reversibly converted to Zn3 (OH)2 V2 O7 ·2H2 O in ZnSO4 electrolyte, followed by Zn 2+ (de-)intercalation into both phases upon cycling, thus enabling full utilization of the bulk electrode and realizing maximization of the specific capacitance (460 F g −1 at 1 A g −1 current density). When cycled in Al2 (SO4 )3 electrolyte, the large VO2 (B) nanobelts collapse into small pellets due to the strong electrostatic force between the Al 3+ ions and host structure, thereby resulting in serious structural instability and inferior pseudocapacitive properties. In general, this work provides valuable insights in understanding the behaviors of mono/multi-valent cations upon intercalation into VO2 (B), which will enable rational design of more layered oxides with excellent charge storage properties or will be extended to other applications.